Digit ratio (2D:4D) moderates the change in handgrip strength on an aggressive stimulus: A study among Polish young adults. (January 2019) - Kociuba, Marek; Chakraborty, Raja; Ignasiak, Zofia; Kozieł, Sławomir
Abstract: Background: The ratio of the lengths of second finger (2D) to the fourth (4D) is a putative indicator of foetal hormonal exposure. The link between 2D:4D and physical strength or sports performance in not consistent. It was suggested that the association of 2D:4D with the sporting and physical ability is better demonstrated in the context of challenge and competition, either real or simulated. However the evidence is limited to a few studies till date. Aim: The objective of this study was to assess whether an aggressive video show could increase muscular strength and if 2D:4D moderated such increase. Study design: We compared outcome measures in two experimental conditions. Outcome measures: Lengths of second (2D) and fourth (4D) digits and their ratio (2D:4D) for both hands, height and weight, handgrip strength of both hands. Subjects: 250 healthy young adults (76 female). Results: The mean left-, right- and average HGS values increased after aggressive video watching than after control blank screen show. The increase was higher in females compared to males. The increase was higher among the individuals with lower 2D:4D, more clearly among females. Conclusions: The 2D:4D correlated negatively with HGS after exposure to challenge condition and this relationship is pronounced in females than males. Thus there is link between prenatal androgenisation and enhanced physical power in challenge situation. Highlights: Hand grip strength is significantly higher after aggressive video watching than after the blank screen show, in both sexes; Hand grip strength after aggressive stimuli depends on 2D:4D ratio in females but not in males; Hand grip strength The link between prenatal testosterone exposure and physical strength depends on the context, such as challenge condition.